2021
DOI: 10.1085/jgp.202012787
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical dysfunction of the sarcomere induced by a pathogenic mutation in troponin T drives cellular adaptation

Abstract: Familial hypertrophic cardiomyopathy (HCM), a leading cause of sudden cardiac death, is primarily caused by mutations in sarcomeric proteins. The pathogenesis of HCM is complex, with functional changes that span scales, from molecules to tissues. This makes it challenging to deconvolve the biophysical molecular defect that drives the disease pathogenesis from downstream changes in cellular function. In this study, we examine an HCM mutation in troponin T, R92Q, for which several models explaining its effects i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 82 publications
3
29
0
1
Order By: Relevance
“…, 2014 ; Clippinger et al. , 2019 , 2021 ). Thus, altered kinetics of actomyosin dissociation are not responsible for the decreased calcium sensitivity observed in the in vitro motility assay ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2014 ; Clippinger et al. , 2019 , 2021 ). Thus, altered kinetics of actomyosin dissociation are not responsible for the decreased calcium sensitivity observed in the in vitro motility assay ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…TnC carrying three mutations (C35S, T53C, C84S) was expressed, purified, and labeled with 2-(4′-(iodoacetamido)anilino)napthalene-6-sulfonic acid (IAANS; Toronto Research Chemicals) following published protocols ( Davis et al. , 2007 ; Clippinger et al. , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is suggested by a recent review of earlier works [49], and the view is supported by findings in more recent studies that we consider here. Whereas several of these studies report increased twitch forces/cell shortening and/or increased calcium sensitivity for HCM mutations in β-MHC [27,133,179], TnT [134,188,200] actin [32] and cMyBP-C [27,133], this is not consistently found. For example, in one study, Bhagwan [32] (Figure 6) reported increased twitch force, compared to the wild type, of engineered human cardiac tissue for the actin E99K mutant but reduced force for the β-MHC R453C mutant.…”
Section: Studies Using Cardiomyocytes and Cardiac Tissue Engineered F...mentioning
confidence: 94%
“…For thin filament mutations, there does not seem to be generally consistent effects on power, force and velocity under full calcium activation. However, increased calcium sensitivity has been observed as a result of HCM causing mutations in tropomyosin or troponin T, based on ATPase assays [155] and in vitro motility assays [109,[124][125][126]169,[186][187][188][189], using regulated thin filaments. Another effect that has often been observed in the in vitro motility assay, using troponin from HCM patients, is the lack of effects of TnI phosphorylation on Ca 2+ -sensitivity (uncoupling).…”
Section: Different Perspectives Related To Hypo-and Hypercontractilit...mentioning
confidence: 99%
“…Indeed, the molecular mechanisms below the R92Q mutation is a decreased population of the thin filament blocked state, promoting higher force generation during calcium-based activation. The latter represents the initial molecular insult, which leads to multiple downstream alterations, from the expression of genes associated with Ca 2+ handling to EP impairment [65].…”
Section: Hipscmentioning
confidence: 99%